Resiko Bunuh Diri pada Warga Binaan Pemasyarakatan Dewasa dengan Masa Hukuman ≥ 5 Tahun di Lembaga Pemasyarakatan Kelas IIA Palangka Raya: Risk of Suicide in Adult Correctors with a Sentence of ≥ 5 Years in Class IIA Palangka Raya Criminal Institution - Barto Mansyah; Tuti Hariati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Correctional Institutions (Lapas), namely institutions that foster convicts so that they are ready to return to being citizens who comply with the values ​​and legal norms of society. The large number of suicide risk cases is due to the government's lack of attention to the psychological conditions of prisoners or correctional inmates. The causes of suicide are depression, encouragement from the heart, social problems, bad experiences that trigger trauma, and heredity. The purpose of this study was to determine and analyze the risk of suicide as well as the inhibiting and supporting factors for suicide risk in adult prisoners with a sentence of ≥5 years in Palangka Raya Class IIA Penitentiary. This research is case research using qualitative research methods or research based on phenomena that occur intensively in an institution. There is a risk of suicide among prisoners in the Palangka Raya Class IIA Penitentiary, while the supporting factors are the lack of human resources in the field of mental health (psychologists) in the Palangka Raya Class IIA Penitentiary, lack of family trust support, feelings of not accepting the condition and sentence sentences that have been given, the environment of the Class IIA Penitentiary in Palangka Raya which exceeds capacity (overload). Inhibiting factors that affect the risk of suicide in prisoners of correctional services, namely, the existence of facilities for worship in accordance with the beliefs held by each prisoner, the availability of educational facilities, facilities for developing handicrafts, sports facilities such as volly ball, futsal, table tennis, social facilities consisting of from family visits, meeting rooms and family support such as regular visits, giving love, understanding and attention.